TNF causes changes in glomerular endothelial permeability and morphology through a Rho and myosin light chain kinase‐dependent mechanism. Issue 12 (3rd December 2015) - Xu, Chang; Wu, Xiaoyan; Hack, Bradley K.; Bao, Lihua; Cunningham, Patrick N.
Abstract: A key function of the endothelium is to serve as a regulated barrier between tissue compartments. We have previously shown that tumor necrosis factor (TNF) plays a crucial role in lipopolysaccharide (LPS)‐induced acute kidney injury, in part by causing injury to the renal endothelium through its receptor TNFR1. Here, we report that TNF increased permeability to albumin in primary culture mouse renal endothelial cells, as well as human glomerular endothelial cells. This process occurred in association with changes in the actin cytoskeleton and was associated with gaps between previously confluent cells in culture and decreases in the tight junction protein occludin. This process was dependent on myosin light chain activation, as seen by its prevention with Rho‐associated kinase and myosin light chain kinase (MLCK) inhibitors. Surprisingly, permeability was not blocked by inhibition of apoptosis with caspase inhibitors. Additionally, we found that the renal glycocalyx, which plays an important role in barrier function, was also degraded by TNF in a Rho and MLCK dependent fashion. TNF treatment caused a decrease in the size of endothelial fenestrae, dependent on Rho and MLCK, although the relevance of this to changes in permeability is uncertain. In summary, TNF‐induced barrier dysfunction in renal endothelial cells is crucially dependent upon the Rho/MLCK signaling pathway. Abstract : TNF is a key mediator of sepsis, and causes increased macromolecular permeability of renal endothelial cells. Here, we show that this TNF‐induced permeability increase is dependent upon the Rho/MLCK pathway, associated with changes to the actin cytoskeleton. Through Rho and MLCK, TNF causes separation between adjacent endothelial cells, degradation of their glycocalyx, and a possible increase in glomerular fenestrae.